2016
DOI: 10.5812/pedinfect.34435
|View full text |Cite
|
Sign up to set email alerts
|

Procalcitonin Levels Compared With CRP and ESR Levels in Septicemic Children Aged 3 Months to 13 Years in the Pediatric and PICU Wards of Ayatollah Mousavi Hospital, Zanjan

Abstract: Background: Procalcitonin (PCT) levels are increased in sepsis. In most previously conducted research, PCT levels were found to increase during septic shock. Objectives: The purpose of this study was to compare PCT levels with CRP and ESR levels in children with systemic inflammatory response syndrome (SIRS), sepsis, and septic shock. Methods: This cross-sectional study was conducted between December 2011 and December 2012 on 84 children between 3 months and 13 years old admitted in pediatric and PICU wards. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…However, it is crucial to highlight that PCT demonstrates higher specificity in detecting infections when compared to serum CRP and ESR. 15 On the other hand, CRP levels increased in response to various conditions, including systemic inflammations, underlying disorders, and malignant diseases. 16 In addition, our findings indicated that all 22 patients had abnormal WBC counts, which were less than 3,000 cells/µL.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is crucial to highlight that PCT demonstrates higher specificity in detecting infections when compared to serum CRP and ESR. 15 On the other hand, CRP levels increased in response to various conditions, including systemic inflammations, underlying disorders, and malignant diseases. 16 In addition, our findings indicated that all 22 patients had abnormal WBC counts, which were less than 3,000 cells/µL.…”
Section: Discussionmentioning
confidence: 99%
“…Parameters such as the duration of neutropenia and fever correction, length of hospital stay, the need for mechanical ventilation, and the occurrence of death can all be influenced by factors such as the individual patient's condition and underlying disorders, as well as the timely diagnosis and appropriate treatment they receive. 7,15,19 Each patient's unique circumstances and the management they receive play a crucial role in determining the outcomes observed in different studies. It highlights the complexity of these conditions and the importance of personalized care and treatment for each patient.…”
Section: Discussionmentioning
confidence: 99%